How do you solve x^2 = 5x + 2x2=5x+2 by completing the square?

3 Answers

x_1=5/2+sqrt(33)/2~~5.372x1=52+3325.372
x_2=5/2-sqrt(33)/2~~-0.372x2=523320.372

Explanation:

First, bring everything to one side...

x^2 = 5x + 2|-5x-2x2=5x+25x2
rArr x^2 -5x - 2 = 0x25x2=0

Complete the square (a^2+2ab+b^2=(a+b)^2)(a2+2ab+b2=(a+b)2)

x^2-2*5/2x+color(blue)(5^2/2^2-5^2/2^2)-2=0x2252x+522252222=0
(x-5/2)^2-25/4-2=0(x52)22542=0

Solve for xx

(x-5/2)^2-25/4-2=0|+33/4|sqrt()|+5/2(x52)22542=0+334+52
x_(1,2)=5/2+-sqrt(33)/2x1,2=52±332
x_1=5/2+sqrt(33)/2 or x_2=5/2-sqrt(33)/2x1=52+332orx2=52332

Mar 31, 2018

x=5/2+-1/2sqrt33x=52±1233

Explanation:

"rewrite in "color(blue)"standard form"rewrite in standard form

rArrx^2-5x-2=0larrcolor(blue)"in standard form"x25x2=0in standard form

"to solve by the method of "color(blue)"completing the square"to solve by the method of completing the square

• " the coefficient of the "x^2" term must be 1 which it is" the coefficient of the x2 term must be 1 which it is

• " add/subtract "(1/2"coefficient of the x-term")^2" to" add/subtract (12coefficient of the x-term)2 to
x^2-5xx25x

rArrx^2+2(-5/2)xcolor(red)(+25/4)color(red)(-25/4)-2=0x2+2(52)x+2542542=0

rArr(x-5/2)^2-33/4=0(x52)2334=0

rArr(x-5/2)^2=33/4(x52)2=334

color(blue)"take the square root of both sides"take the square root of both sides

rArrx-5/2=+-sqrt(33/4)larrcolor(blue)"note plus or minus"x52=±334note plus or minus

"add "5/2" to both sides"add 52 to both sides

rArrx=5/2+-1/2sqrt33larrcolor(red)"exact solutions"x=52±1233exact solutions

Mar 31, 2018

x=+5/4+-sqrt(33)/2x=+54±332

Explained the concept of completing the square in a lot of detail.
Once you are used to these you can do them in a LOT LESS lines.

Explanation:

Given: x^2=5x+2x2=5x+2

Write as:

x^2-5x-2=yx25x2=y

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("What it is about")What it is about

We are mathematically allowed to change this in any way we chose as long as we incorporate something that takes it back to the original value. As an example suppose we had:

2=t2=t this 'sets in stone' what the relationship is.

Let's totally 'lie' about the relationship by writing

2+34=t2+34=t Now it is wrong. However if we instead write

2+34-34=t2+3434=t it becomes true again.

This concept is used in completing the square. We lie about something to force it into the format we wish to obtain. After obtaining that format we put back in something that turns it into a true statement.
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

We need to have y=x^2-5x+?+k-2y=x25x+?+k2 where the ? is the lie and the kk is the correction

Suppose we make ?=-5/2?=52

y=(x^2-5x-5/2)+k-2" ".........Equation(1)

We can factorise the brackets giving:

y=(x-5/2)^2 +color(mediumblue)(k)-2" "......Equation(2)color(green)( larr" our objective")

If you multiply out the brackets we get Eqn(1) (includes the lie)

color(white)("ddd")color(green)("We want ")
color(white)("dddd")color(green)("this bit")color(red)(color(white)("ddd")"The lie")
color(green)( color(white)("dddddd")darr)color(red)(color(white)("ddddd.d")darr)
y=obrace(x^2-5x)+ubrace(obrace((-5/2)^2)+k)color(white)("d")-2
color(green)(color(white)("dddddddddddddddd")uarr)
color(green)(color(white)("ddddddddd")"The lie with correction")

So for this to work we set (-5/2)^2+k=0" " Add 0 and nothing changes so this action neutralises the lie.

Thus color(mediumblue)(k=-25/4)

Substitute for color(mediumblue)(k) in Equation(2)

color(green)(y=(x-5/2)^2+color(white)("dd")color(mediumblue)(k)-2

color(green)(y=(x-5/2)^2+ubrace(color(mediumblue)((-25/4))-2))

y=(x-5/2)^2color(white)(".d.dd")-33/4

YOU HAVE NOW COMPLETED THE SQUARE
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Set

y=0=(x-5/2)^2-33/4

(x-5/2)^2=+33/4

x-5/4=+-sqrt(33/4)

x=+5/4+-sqrt(33)/2